On a Hypersurface of a Finsler Space with Randers Change of Matsumoto Metric. (26th June 2013) - Gupta, M. K.; Singh, Abhay; Pandey, P. N.
Abstract : The present paper contains certain geometrical properties of a hypersurface of a Finsler space with Randers change of Matsumoto metric.